2017
DOI: 10.1002/2016jc012130
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability of the Eastern Tropical Pacific Fresh Pool

Abstract: The Eastern Pacific Fresh Pool (EPFP) is a large region of low sea surface salinity (SSS) defined by values lower than 34 practical salinity scale within (5°S–30°N, 75°W–180°W). The fresh pool dynamically responds to strong regional and seasonally varying ocean‐atmosphere‐land interactions (including monsoon rain, trade and gap winds, and strong currents). Using more than 5 years of Soil Moisture and Ocean Salinity (SMOS) satellite sea surface salinity (SSS) and complementary satellite wind, rain, currents, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 40 publications
(61 reference statements)
1
53
0
Order By: Relevance
“…The 5–10°N SSSAs are subsequently advected north by the Ekman drift into the westward flowing NEC and then north out of it again. The westward advection of the EPFP does not appear to play a major role in the 5–10°N SSS anomaly, as suggested by Guimbard et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5–10°N SSSAs are subsequently advected north by the Ekman drift into the westward flowing NEC and then north out of it again. The westward advection of the EPFP does not appear to play a major role in the 5–10°N SSS anomaly, as suggested by Guimbard et al ().…”
Section: Discussionmentioning
confidence: 99%
“…It is also the most powerful El Niño monitored by the fully deployed Argo program (Corbett et al, ; Gasparin & Roemmich, ). Guimbard et al () observed the extent of the EPFP (less than 34.5 in their study) to be 20% larger in 2015 than the climatology and to reach the dateline by the end of 2015. During the previous rainy season the preconditioning in 2014 of the zonal extension of the EPFP was found to be an essential factor enabling the development of the 2015 maxima.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal SSS signal created by intense precipitation associated with the ITCZ is then advected poleward by the Ekman transport (Bingham & Lee, ; Yu, ). Equatorial surface currents were found to be crucial in the seasonal zonal extension of the freshpool (Guimbard et al, ). The NECC brings saltier waters in January–April, whereas to its north and south, the NEC and SEC advect fresher waters westward, away from the coastal area.…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of the large-scale salinity field is known as the Eastern Pacific Fresh Pool. This region of the Eastern Pacific has low surface salinity (<34 g kg -1 ) that is maintained by an interplay between the northsouth annual migration of rainfall associated with the ITCZ and the annual cycle of the equatorial zonal current system (Alory et al, 2012;Guimbard et al, 2017). In particular, recent results from satellitederived products indicate that uncertainties in Ekman advection and mixed-layer entrainment/detrainment processes are among the main obstacles to accurately predicting the North Pacific ITCZ freshwater balance (Guimbard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This region of the Eastern Pacific has low surface salinity (<34 g kg -1 ) that is maintained by an interplay between the northsouth annual migration of rainfall associated with the ITCZ and the annual cycle of the equatorial zonal current system (Alory et al, 2012;Guimbard et al, 2017). In particular, recent results from satellitederived products indicate that uncertainties in Ekman advection and mixed-layer entrainment/detrainment processes are among the main obstacles to accurately predicting the North Pacific ITCZ freshwater balance (Guimbard et al, 2017). The SPURS-2 Coordinated Lagrangian Drift experiment gives new insight into these processes by following the surface water masses on their eastward progress through the ITCZ and documenting both the accumulation of freshwater precipitation and its incorporation into the seasonal halocline.…”
Section: Discussionmentioning
confidence: 99%